Clinical Relapses of Atypical HUS on Eculizumab: Clinical Gap for Monitoring and Individualised Therapy. (6th February 2018) - Teoh, Chia Wei; Gorman, Kathleen Mary; Lynch, Bryan; Goodship, Timothy H. J.; Dolan, Niamh Marie; Waldron, Mary; Riordan, Michael; Awan, Atif
Abstract : Atypical hemolytic uremic syndrome (aHUS) is caused by dysregulation of the complement system. A humanised anti-C5 monoclonal antibody (eculizumab) is available for the treatment of aHUS. We present the first description of atypical HUS in a child with a coexistent diagnosis of a POL-III leukodystrophy. On standard eculizumab dosing regime, there was evidence of ongoing C5 cleavage and clinical relapses when immunologically challenged. Eculizumab is an effective therapy for aHUS, but the recommended doses may not be adequate for all patients, highlighting the need for ongoing efforts to develop a strategy for monitoring of treatment efficacy and potential individualisation of therapy.